Cooperative Learning Model to Improve Learning Outcomes of Grade V PE Using E-Modules - Iswarini, Septi; Riswandi, Riswandi; Kurniawan, Candra; Herpratiwi, Herpratiwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research aims to develop technology-based e-modules to improve student learning outcomes in Physical Education and Health (PJOK) subjects. The method applied is the ADDIE development model, which includes the stages of needs analysis, design, development, and product evaluation. Data were collected through interviews, questionnaires, and formative test instruments, which were then validated by material, media, and design experts. The results showed that the development of an e-module-based cooperative learning model for Physical Education subjects at SDN 1 Sukaraja was very effective in improving the learning outcomes of grade V students. The application of the ADDIE approach in the development process ensures the quality of materials, media, and learning designs that are feasible and attractive, with the average feasibility assessment results reaching 87.67%, which is included in the very feasible category. The implementation of this model is proven to improve learning outcomes significantly, with the effectiveness rate increasing from 50.56% in the pretest to 91.56% in the posttest, as well as the N-Gain showing the majority of learners experienced a substantial increase in learning outcomes. The model also strengthened learners’ social cooperation and skills in the learning process, in line with the characteristics of Physical Education learning. In addition, validation by experts showed that the developed e-module meets pedagogical and technological standards that can support a more interactive and enjoyable learning process.